2016
DOI: 10.1097/fbp.0000000000000190
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal exposure to benzyl butyl phthalate induces alterations in neuronal development/maturation protein expression, estrogen responses, and fear conditioning in rodents

Abstract: Phthalate exposure has recently been associated with behavioral actions that are linked to its endocrine-disrupting properties. The purpose of this study was to investigate the molecular, anatomical, and behavioral effects of indirect perinatal benzyl butyl phthalate (BBP) exposure in offspring of BBP-treated pregnant dams. In two separate experiments, we administered BBP (10.0 μg/ml) on food pellets to pregnant dams and examined the offspring. The first experiment revealed reproductive anatomical abnormalitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Four other studies assessed the effects of exposure to lower doses of phthalates with BBP at 10 µg/kg/d, DEHP at 33 mg/kg/d, or a phthalate mixture at 0.2 to 1 mg/kg/d on aversive stimulus associated learning [ 82 ], object recognition memory [ 83 ], and cognitive flexibility [ 72 , 84 ], respectively. In mice, the novel object recognition test indicated a higher preference for the novel object in mice exposed to 200 mg/kg/d [ 83 ].…”
Section: Behavioral and Neural Effects Of Phthalate Exposurementioning
confidence: 99%
See 2 more Smart Citations
“…Four other studies assessed the effects of exposure to lower doses of phthalates with BBP at 10 µg/kg/d, DEHP at 33 mg/kg/d, or a phthalate mixture at 0.2 to 1 mg/kg/d on aversive stimulus associated learning [ 82 ], object recognition memory [ 83 ], and cognitive flexibility [ 72 , 84 ], respectively. In mice, the novel object recognition test indicated a higher preference for the novel object in mice exposed to 200 mg/kg/d [ 83 ].…”
Section: Behavioral and Neural Effects Of Phthalate Exposurementioning
confidence: 99%
“…In the aversive-stimulus associative test, a shorter duration of freezing during the interval period and the tone period was observed in rats exposed to BBP at 10 µg/kg/d [ 82 ]. Analyses of the hippocampus and amygdala, the two regions involved in this behavior, showed increased amounts of synapsin-1 in the dorsal hippocampus and lower amounts of ERα and MeCP2 protein in the amygdala [ 82 ].…”
Section: Behavioral and Neural Effects Of Phthalate Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…A model of maternal perinatal exposure to BBP was performed in rodents by the group of DeBartolo and colleagues (DeBartolo et al, 2016). In this study, it was observed that the BBP‐exposed offspring had learning and memory impairments, that were accompanied by molecular abnormalities in multiple brain regions (DeBartolo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A model of maternal perinatal exposure to BBP was performed in rodents by the group of DeBartolo and colleagues (DeBartolo et al, 2016). In this study, it was observed that the BBP‐exposed offspring had learning and memory impairments, that were accompanied by molecular abnormalities in multiple brain regions (DeBartolo et al, 2016). On the other hand, in order to make an exposure model closer to what happens with the daily use of plastics, Kougias, Sellinger, Willing, and Juraska (2018) performed in rats an experimental approach to evaluate the long‐term neurological effects derived from perinatal exposure to an environmentally relevant mixture of phthalates.…”
Section: Introductionmentioning
confidence: 99%